Endoscopic Ear Surgery in Dhulikhel Hospital: A decade of Experience - Shrestha, B. L. (Kathmandu University Medical Journal, 2022)
Endoscopic ear surgery is one of the most commonly performed surgeries in Dhulikhel hospital. In the past eleven years, there have been different endoscopic ear surgeries performed with a very good outcome. The main benefit of endoscopic ear surgery is; to let the surgeon see better, proceed with the surgery through the trans-canal, teaching and training of the students. There are some drawbacks of endoscopic ear surgery like the one-handed technique and learning curve. With repeated practice and the help of motion parallax, the trainee can overcome the drawback of the procedure.